2020
DOI: 10.1002/mp.14498
|View full text |Cite
|
Sign up to set email alerts
|

A generative adversarial network‐based (GAN‐based) architecture for automatic fiducial marker detection in prostate MRI‐only radiotherapy simulation images

Abstract: Purpose Clinical sites utilizing magnetic resonance imaging (MRI)‐only simulation for prostate radiotherapy planning typically use fiducial markers for pretreatment patient positioning and alignment. Fiducial markers appear as small signal voids in MRI images and are often difficult to discern. Existing clinical methods for fiducial marker localization require multiple MRI sequences and/or manual interaction and specialized expertise. In this study, we develop a robust method for automatic fiducial marker dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A limitation of this study is that it relies on the assumption that fiducial markers can be identified with good accuracy in MRI images. Much work has been done on the selection of optimal MRI sequences, optimal fiducial markers and detection methods for fiducial markers in MRI 10,18,19,35–37 . The goal of many of these studies was to identify fiducial markers for identification at simulation with the eventual goal of voxel burning the fiducial locations in DRR images for pretreatment positioning and alignment using C‐arm linacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is that it relies on the assumption that fiducial markers can be identified with good accuracy in MRI images. Much work has been done on the selection of optimal MRI sequences, optimal fiducial markers and detection methods for fiducial markers in MRI 10,18,19,35–37 . The goal of many of these studies was to identify fiducial markers for identification at simulation with the eventual goal of voxel burning the fiducial locations in DRR images for pretreatment positioning and alignment using C‐arm linacs.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic radiosurgery platforms use fiducial tracking algorithms to detect fiducial markers for tumor localization on orthogonal X‐ray images for IGRT‐based tracking 14,17 . Fiducial markers appear as small dark signal voids on MRI and cannot be directly used with robotic radiosurgery fiducial marker tracking software 18–20 . For the clinical use of MRI‐only simulation with standard C‐arm linear accelerator (linac)‐based treatments, fiducials identified on MRI are voxel burned at the same location in their corresponding sCT images 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Pix2pix GAN is a classical deep learning network for image-to-image translation, with a comparable performance to that of other methods. [28][29][30] However, it does not perform well for predicting different rotation positions from supine scanned images, which may explain why it is not a simple image-to-image translation task. The same architecture of pix2pix GAN has been developed for pseudo-CT synthesis from the corresponding MRI by our research group.…”
Section: Discussionmentioning
confidence: 99%
“…In MRI images, fiducial markers display as tiny-signal voids and are usually challenged to localized in images. The proposed approach relies on deep learning to automatically detect tinysignal fiducial features in scan images [152]. Segmenting the prostate accurately by using MRI images is a challenging research area in prostate cancer diagnosis.…”
Section: Gans Applications In Multi-organ Segmentationmentioning
confidence: 99%